Motorisation croissante et évolution des déplacements domicile-travail à Rio de Janeiro entre 2002 et 2012 - Benjamin Motte-Baumvol (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
This paper analyses the general increase in distances and duration of commuting based on the Household Surveys of 2002 and 2012 from the Rio de Janeiro Metropolitan Area. This increase is unequal between populations, depending in particular on the area of residence and level of education. However, even if the populations with low educational levels and residing in the poorest neighborhoods experience high commute durations, the most significant increases in travel times concern the inhabitants of new neighborhoods or towns occupied by the upper middle class, such as Barra da Tijuca and Niterói.